"PhysioLego:" Learning concepts, building, and applying physiology knowledge - Hwee-Ming Cheng; See-Ziau Hoe (Wolters Kluwer Medknow Publications, 2020)
When we talk about conceptual learning, we also think about certain principles in physiology that recur in various organ systems in the body. These global underlying themes are like the Lego building blocks when we look at the mechanics of physiological processes. One main?" PhysioLego" concept of building brick is the relationship between membrane selective permeability and effective osmotic pressure. This is expressed in laboratory class demonstration by saying that the tonicity of a solution is dependent on not just the osmotic concentration but also importantly on the membrane penetrability of the solute in solution. The "PhysioLego" osmotic bricks and its construction to build an integrated understanding of physiology and pathophysiology will be described in this article.